Application of Failure Mode and Effect Analysis (FMEA) and Fishbone Diagram in the Analysis of Engine Component Failure on Harbour Mobile Crane - Khairansyah, Mades Darul; Dhani, Mey Rohma; Syahputra, Viandra Trisna (Tibuana, 2026)
Container loading and unloading port is a port that uses Harbour Mobile Crane (HMC) as its main tool in the container loading and unloading process, and operates 24 hours. The high work intensity causes the HMC engine components to be susceptible to failure, thus disrupting the smooth operation of operational activities. This study aims to analyze the failure of Harbour Mobile Crane (HMC) engine components in a container loading and unloading service company using the Failure Mode and Effect Analysis (FMEA) and Fishbone Diagram methods. The FMEA method is used to identify engine component failures and determine the Risk Priority Number (RPN) value, while the fishbone diagram is used to identify the root cause of failure and determine recommendations. The results of the FMEA analysis on 7 engine components, the highest RPN value is found in the fuel filter component with an RPN value of 105. Furthermore, the component with the highest RPN value is analysed using a fishbone diagram to determine the root cause in terms of people, method, machines, material, measurements, management, environment, and maintenance factors. The results of the fishbone diagram analysis are used as a reference for providing recommendations using the risk control hierarchy, namely elimination, substitution, engineering, administrative control, and personal protective equipment.